Post-meiotic nucleo-cytoplasmic interaction in Cosmos bipinnatus : Early events at the nuclear envelope. - Dickinson, H; Potter, U (Springer-Verlag, 1979)
An interaction involving the nuclear envelope and spherical double-membrane bound inclusions takes place in the cytoplasm of post-meiotic male microspores of Cosmos (tribe Heliantheae, sub-tribe Coreopsidinae). The identity of the spherical inclusions has yet to be fully established, but they closely resemble profiles elsewhere in the cytoplasm, themselves presumably derived from the mitochondrial population of the premeiotic pollen mother cells. Both the cytoplasmic and nucleaar-associated inclusions regularly contain a central 'vesicle', formed by an ingagination of their bounding membranes. The interaction, which occurs immediately prior to the deposition of the primexine of the pollen wall, involves the adhesion of the inclusions to the nuclear surface. Experiments with osmotically disrupted cells reveal that the inclusions are firmly bound to the envelope and, at the points of contact, electron opaque granules are regularly present. Frequently elements of the chromatin may be observed in juxtapostion to these points of contact, but on the inner face of the envelope. The interaction in Cosmos is proposed to constitute part of the process by which the cytoplasm and its content are realigned to the new "gametophylic" style of growth.